Effects of dapagliflozin on prevention of major clinical events and recovery in patients with respiratory failure because of COVID‐19: Design and rationale for the DARE‐19 study. Issue 4 (19th January 2021) - Kosiborod, Mikhail; Berwanger, Otavio; Koch, Gary G.; Martinez, Felipe; Mukhtar, Omar; Verma, Subodh; Chopra, Vijay; Javaheri, Ali; Ambery, Philip; Gasparyan, Samvel B.; Buenconsejo, Joan; Sjöström, C. David; et al.
Abstract: Aims: Coronavirus disease 2019 (COVID‐19) is caused by a novel severe acute respiratory syndrome coronavirus 2. It can lead to multiorgan failure, including respiratory and cardiovascular decompensation, and kidney injury, with significant associated morbidity and mortality, particularly in patients with underlying metabolic, cardiovascular, respiratory or kidney disease. Dapagliflozin, a sodium‐glucose cotransporter‐2 inhibitor, has shown significant cardio‐ and renoprotective benefits in patients with type 2 diabetes (with and without atherosclerotic cardiovascular disease), heart failure and chronic kidney disease, and may provide similar organ protection in high‐risk patients with COVID‐19. Materials and methods: DARE‐19 (NCT04350593) is an investigator‐initiated, collaborative, international, multicentre, randomized, double‐blind, placebo‐controlled study testing the dual hypotheses that dapagliflozin can reduce the incidence of cardiovascular, kidney and/or respiratory complications or all‐cause mortality, or improve clinical recovery, in adult patients hospitalized with COVID‐19 but not critically ill on admission. Eligible patients will have ≥1 cardiometabolic risk factor for COVID‐19 complications. Patients will be randomized 1:1 to dapagliflozin 10 mg or placebo. Primary efficacy endpoints are time to development of new or worsened organ dysfunction during index hospitalization, or all‐cause mortality, and the hierarchical composite endpoint of change in clinical status through day 30 of treatment. Safety of dapagliflozin in individuals with COVID‐19 will be assessed. Conclusions: DARE‐19 will evaluate whether dapagliflozin can prevent COVID‐19‐related complications and all‐cause mortality, or improve clinical recovery, and assess the safety profile of dapagliflozin in this patient population. Currently, DARE‐19 is the first large randomized controlled trial investigating use of sodium‐glucose cotransporter 2 inhibitors in patients with COVID‐19.